2005
DOI: 10.1007/s10346-004-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intense rainfall on the activity of large-scale crystalline schist landslides in Shikoku Island, Japan

Abstract: Many large landslides in the crystalline schist region of Shikoku Island, Japan, are susceptible to intense rainfall. Through the use of on-site monitoring systems, the activity of landslides and their meteorological triggers can be assessed. Continuous high-intensity rainfall was found to play a key role in provoking landslide movement. This paper investigates the influence of intense rainfall on the activity of crystalline schist landslides by examining rainfall and displacement of four typical landslides. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 6 publications
0
71
1
Order By: Relevance
“…At regional scale, warning systems for rainfall-induced landslides are mainly based on empirical rainfall thresholds (Keefer et al, 1987;Aleotti, 2004;Hong et al, 2005;Tiranti and Rabuffetti, 2010;Baum and Godt, 2010;Capparelli and Tiranti, 2010;Cannon et al, 2011;Floris et al, 2012;Jakob et al, 2012;Staley et al, 2013;Lagomarsino et al, 2013;Tiranti et al, 2014;Cucchi et al, 2015). A broad literature exists on empirical rainfall thresholds for the possible initiation of landslides (Guzzetti et al, 2007, and references therein), and intensity-duration (I -D) thresholds are the most popular (Caine, 1980;Guzzetti et al, 2008;and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…At regional scale, warning systems for rainfall-induced landslides are mainly based on empirical rainfall thresholds (Keefer et al, 1987;Aleotti, 2004;Hong et al, 2005;Tiranti and Rabuffetti, 2010;Baum and Godt, 2010;Capparelli and Tiranti, 2010;Cannon et al, 2011;Floris et al, 2012;Jakob et al, 2012;Staley et al, 2013;Lagomarsino et al, 2013;Tiranti et al, 2014;Cucchi et al, 2015). A broad literature exists on empirical rainfall thresholds for the possible initiation of landslides (Guzzetti et al, 2007, and references therein), and intensity-duration (I -D) thresholds are the most popular (Caine, 1980;Guzzetti et al, 2008;and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also found that peak rainfall intensity and the initiation of mass movements are often concurrent (Aleotti 2004;Chien-Yuan et al 2005;Guzzetti et al 2007Guzzetti et al , 2008Dahal and Hasegawa 2008;Saito et al 2010aSaito et al , 2010b. Although antecedent rainfall also plays an important role in the initiation of mass movement (Kim et al 1992;Glade 1997;Crozier 1999;Glade et al 2000;Guzzetti et al 2007Guzzetti et al , 2008Dahal and Hasegawa 2008), intensity-duration (I-D) thresholds and/or the peak rainfall intensity are often used to predict mass movements and warn the appropriate authorities of potential mass movement hazards (Onodera et al 1974;Keefer et al 1987;Aleotti 2004;Hong et al 2005;Cannon et al 2008;Coe et al 2008;Dahal and Hasegawa 2008;Guzzetti et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them evaluated the role played by conditioning factors and triggering mechanisms in different environments and scales (e.g. Pachauri and Pant, 1992;Corominas et al, 2004;Hong et al, 2005). Other studies analysed the influence of external factors such as deforestation (e.g.…”
Section: Introductionmentioning
confidence: 99%